Coating of Biomaterial Scaffolds with the Collagen-Mimetic Peptide GFOGER for Bone Defect Repair - Wojtowicz, Abigail M. (2009)
Healing large bone defects and non-unions remains a significant clinical problem. Current treatments, consisting of auto- and allografts, are limited by donor supply and morbidity, insufficient bioactivity and risk of infection. Biotherapeutics, including cells, genes and proteins, represent promising alternative therapies, but these strategies are limited by technical roadblocks to biotherapeutic delivery, cell sourcing, high cost, and regulatory hurdles. In the present study, the collagen-mimetic peptide, GFOGER, was used to coat synthetic PCL scaffolds to promote bone formation in critically-sized segmental defects in rats. GFOGER is a synthetic triple helical peptide that binds to the α2β1 integrin receptor involved in osteogenesis. GFOGER coatings passively-adsorbed onto polymeric scaffolds, in the absence of exogenous cells or growth factors, significantly accelerated and increased bone formation in non-healing femoral defects compared to uncoated scaffolds and empty defects. Despite differences in bone volume, no differences in torsional strength were detected after 12 weeks, indicating that bone mass but not bone quality was improved in this model. This work demonstrates a simple, cell/growth factor-free strategy to promote bone formation in challenging, non-healing bone defects. This biomaterial coating strategy represents a cost effective and facile approach translatable into a robust clinical therapy for musculoskeletal applications.